ACADEMIC DIPLOMACY OF EDUCATIONAL INSTITUTIONS’ HEADS AS A TOOL OF CREATIVE COOPERATION - Pyshchyk, Olena (Educological discourse, 2021)
The article is devoted to the problem of educational institutions’ heads’ academic diplomacy development by creative cooperation means. The main task of educational diplomacy in forming the educational institution image and all participants’ interpersonal relations in the educational process is substantiated. The attention is focused on the educational institutions’ heads’ communicative activity as a phenomenon and creativity pedagogy subject; the educational institutions’ heads’ creativity directions are substantiated; considered the concepts theoretical content of «diplomacy», «communicative culture», «educational diplomacy», «creativity»; diagnostics the readiness of educational institutions’ leaders and teachers for the educational diplomacy development as a tool for the creativity pedagogy was carried out. The diplomatic qualities of the leader and teachers of an educational institution are characterized, which provide an opportunity for the manifestation of their own creative abilities and characteristics, which encourage the creative potentials to be processed in a high-quality, enrich them with mental new formations, creative activity experience, and creative abilities, and also develop communicative interaction. The direction of interaction between the educational process participants on the dialogue basis and the head preparation for the creation of psychological and pedagogical conditions, concerning the creative educational activity of students, with educational diplomacy application, communication methods and receptions of their creative activity is defined. Pedagogical creativity occupies a special place among different types of creativity, because it determines the dynamic development vectors of mankind all creative processes, and the creative nature development is determined by communication and increase in communicative culture. The peculiarity of any communicative process – the process as a result of which a qualitatively new one is created – is that not only man, the creator influences his own creativity result, but also the subject of creative interaction contributes to further human development. That is why in the pedagogical interaction process the creative development of the educational institutions’ heads is both their activity purpose and the creative development means of the leader’s personality, increasing his professional competence and communicative skills level. Thus, creativity leads to professional and personal self-realization of the leader in the management process.